The role of the thalamus in focal human epilepsy: insights from stereoelectroencephalography (SEEG) - Feys, Odile; Pizzo, Francesca; Makhalova, Julia; Carron, Romain; Bartolomei, Fabrice (Frontiers in Neurology, 2025)
This review explores the role of the thalamus in focal epilepsy, focusing on insights gained from stereoelectroencephalography (SEEG). The thalamus has recently regained attention as a crucial player in seizure dynamics. Thalamic SEEG recordings can be used to assess certain aspects of the thalamus’s role in human focal epilepsy, in particular the timing and dynamics of involvement of distinct thalamic nuclei during seizures and in interictal activity. Estimation of thalamic involvement in seizure propagation may be valuable before embarking on surgical resection and provide guidance for neuromodulation strategies. High thalamic epileptogenicity correlates with poorer surgical outcomes, making it a predictive biomarker. Deep brain stimulation (DBS), particularly targeting the anterior and pulvinar nuclei, has effectively reduced seizure frequency and improved consciousness during seizures. However, the effectiveness of DBS varies, emphasizing the need for individual targeting based on individual seizure dynamics. High-frequency thalamic stimulation can reduce seizure frequency and alter epileptogenic networks, offering tailored therapeutic approaches. Despite the potential added surgical risks of depth electrode implantation, thalamic SEEG significantly enhances the understanding of epileptogenic networks. It supports the development of personalized epilepsy treatments by elucidating the complex interplay between cortical and subcortical regions, paving the way for improved seizure management and neuromodulation strategies.